Improving Livelihoods through Youth-Adult Partnerships involving School-based,Agripreneurship Projects: The Experiences of Adult Partners in Uganda - Stephen C. Mukembo; M. Craig Edwards (Journal of International Agricultural and Extension Education, 2020)
The increasing number of unemployed and underemployed youth across the globe, especially indeveloping countries, has reached alarming levels. In Africa, for example, this phenomenon hasled to some youth making treacherous journeys across the Mediterranean Sea to Europe and other parts of the world in search of better livelihoods. Such an influx of immigrants, primarily to Europe and North America, has caused resentment and outcries by many citizens of the affected nations. Some of these challenges, however,could be allayed by engaging youth in income-generating projects, including agricultural entrepreneurship, i.e., agripreneurship,tocreate jobs and improve livelihoods. This maybe achieved through Youth-Adult Partnerships (Y-APs) by which youth and adults work together on agricultural projects of mutual interest. This study explored the experiences of adult partners in Uganda who collaborated with youth on their school-based, agripreneurial projects (SAPs) involving the raising of broiler chickens. Because of their partnership working on SAPs, both the youths’and adults’ knowledge and understanding of concepts related to agripreneurship and raising of broilers chickens improved. The need exists to provide an enabling environment to promote an agripreneurial culture among youth through Y-APs if we seek to inspire them to pursue agripreneurship and related opportunities for job creation while also enabling the food security of communities and improved livelihoods for their citizens.
Keywords: agripreneurship; improving livelihoods; project-based learning; school-basedagripreneurial projects; youth unemployment; youth-adultpartnerships